AN ANALYSIS OF COMMUNICATION STRATEGIES USED BY THE PEOPLE INVOLVED IN NGIDIH WEDDING CEREMONY IN PADANGBULIA VILLAGE - ., I Gusti Ayu Ketut Yustriantari; ., Prof. Dr.I Ketut Seken,MA; ., Drs. I Wayan Suarnajaya,MA., Ph.D. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This study aimed at (1) investigating and analyzing the types of communication strategies used by the people involved in Ngidih wedding ceremonny and (2) knowing the motives of the use communication strategies in Ngidih wedding process. The subjects of this study were two kelian adat, two kelian dinas, pangeter, groom’s and bride parents in Padangbulia village. The data were collected by using the researcher as the main instrument helped by some devices, namely non-participant observation, audio-video recorder, interview and field note. The types of communication strategies were gathered by observing and recording the people involved during Ngidih wedding process, while the interview guides were used to gather the data about the motives in using the types of communication strategies used by the respondents. The results of this study showed that there were 9 types of communication strategies used by prajuru (manggala desa), groom’s and bride’s family. Mime strategy was the most frequently used by prajuru (manggala desa), groom’s and bride’s family. The motives of using those strategies among the respondents were intented to make everthing clear and acceptable. They also said that it was usually shown naturally by them in order to emphasize the aims, and they used gesture or facial expression to express their feeling in their speech. The used of gesture was believed to be able to make the interaction much calmer and more relax in using communication strategies during Ngidih wedding process.keyword : communication strategies, ngidih wedding ceremony, balinese hinduism marriage